2014
DOI: 10.1007/s13139-014-0301-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 18F-FDG PET/CT as a Prognostic Factor in Patients with Synovial Sarcoma

Abstract: Purpose This research aims to investigate the potential of 18 Ffluorodeoxyglucose positron emission tomography/computed tomography (FDG PET) to predict pathologic response after neoadjuvant chemotherapy (NAC) and overall survival (OS) of patients with synovial sarcoma in Korea. Methods Twenty patients with synovial sarcoma from January 2001 to December 2011 were reviewed retrospectively. All patients underwent pre-treatment FDG PET and tumor removal. Patients were classified with the maximum SUV (SUVmax), meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
0
22
2
2
Order By: Relevance
“…Thyroid volume was measured using the transaxial CTimages. The functional thyroid mass was then defined as the product of SUVmean and thyroid volume, which was conceptually the same as used for a metabolic tumor volume of F-18 fluorodeoxyglucose PET study ( 18 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…Thyroid volume was measured using the transaxial CTimages. The functional thyroid mass was then defined as the product of SUVmean and thyroid volume, which was conceptually the same as used for a metabolic tumor volume of F-18 fluorodeoxyglucose PET study ( 18 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…All 11 studies indicated high SUVmax, MTV, or/and TLG represented a worse prognosis than patients with low numerical value. In terms of association between PET parameters and OS and PFS, there are 7 studies [ 13 , 18 23 ] that only provided with prognostic information about SUVmax and 4 studies [ 11 , 12 , 24 , 25 ] analyzed prognostic value of MTV and TLG. The major characteristics of 11 publications are summarized in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, there are several contradictions existing in included studies of this meta-analysis. There existed a study [ 11 ] which reported significant association between pretherapeutic higher SUVmax, higher MTV, higher TLG and poorer OS in patients with synovial sarcoma. However, in another study, [ 13 ] SUVmax was regarded as a significant independent prognostic marker for OS in STS while MTV and TLG failed to provide with significant prognostic information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical significance of volume-based PET parameters has been actively investigated in several kinds of malignancies including lung cancer. 29 33 The prognostic significance of volumetric PET parameters in SCLC has been also analyzed by several investigations. 20 , 21 , 24 In their subgroup analysis of LS-SCLC, Zhu et al 20 and Oh et al 21 demonstrated that patients with larger MTVs had significantly shorter median OS and PFS compared with those with smaller MTVs, as revealed by Kaplan–Meier survival curves.…”
Section: Discussionmentioning
confidence: 99%